2005
DOI: 10.1007/11545156_13
|View full text |Cite
|
Sign up to set email alerts
|

When Technology Meets the Mind: A Comparative Study of the Technology Acceptance Model

Abstract: Abstract. Issues related to technology, including diffusion, acceptance, adoption, and adaptation, have been the focus of research for different disciplines including Information Systems (IS), System Dynamics, Psychology, and Management Science. Of all research conducted and models developed to study technology related issues, the Technology Acceptance Model (TAM) stands out as most prominent, particularly in the field of IS. However, technology acceptance research has been relatively limited in its applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
0
26
0
4
Order By: Relevance
“…In relation to the factor of the implementation environment, it involves the organizational characteristics (Dadayan and Ferro, 2005;Nanayakkara, 2007), whilst it is the technology characteristics that are associated with the factor of the technology. Measurement of these characteristics was made by examining the ease of use and the usefulness of the technology (Dadayan and Ferro, 2005;Nanayakkara, 2007;Venkatesh et al, 2003). For this study, the factor of the implementation environment was measured by way of two variables: social influence; and the facilitating conditions.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the factor of the implementation environment, it involves the organizational characteristics (Dadayan and Ferro, 2005;Nanayakkara, 2007), whilst it is the technology characteristics that are associated with the factor of the technology. Measurement of these characteristics was made by examining the ease of use and the usefulness of the technology (Dadayan and Ferro, 2005;Nanayakkara, 2007;Venkatesh et al, 2003). For this study, the factor of the implementation environment was measured by way of two variables: social influence; and the facilitating conditions.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Of note is that the uptake of mobile technology is more personalized in relation to the individual (Carlsson et al, 2006). However, it has been claimed the UTAUT does not take into consideration the factor of an individual's characteristics as claimed by Dadayan and Ferro (2005) and Nanayakkara (2007). Accordingly, this paper has included the individual factor in order to ascertain an individual's characteristics such as their knowledge and level of skills and their perceptions such as their capacity to utilize m-learning in a meaningful way.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Raitoharju suggests that the stress levels inherent in healthcare work needed to be added to TAM to provide a more predictive model (27). This is supported within wider domains by arguments that greater use of qualitative research methods to understand the significance of people, organisational issues and context in technology acceptance is needed particularly in relation to the public sector (23). Following a literature review Yarborough and Smith found that studies confirmed the appropriateness of TAM amongst physicians but the "perceived ease of use" construct was not fully supported and suggested that in addition to time issues a collaborative organisational culture that emphasises teamwork is needed for successful implementation of IT based systems into physicians practices (28), (29).…”
Section: Application Of Tam and Its Variants In Healthcarementioning
confidence: 99%
“…This is consistent with DeSanctis (1983), who linked high levels of systems expectations with highly positive use of that system. In much of the TAM research, user expectancy is often measured as "perceived performance" (Bhattacherjee, 2001;D'Ambra & Wilson, 2004;Dadayan & Ferro, 2005), and ranks consistently as one of the strongest predictors of user BI (Wang, Wu & Wang, 2008).…”
Section: Expectancy: Some Observations and Discussionmentioning
confidence: 99%